Observations and Studies on the Transiting Systems HAT-P-36, XO-2 and WASP-76 - Weilong Wang; Shenghong Gu; Xiaobin Wang; Leilei Sun; Byeong-Cheol Lee; Chi-Tai Kwok; Ho-Keung Hui; Jiangpei Dou; Yue Xiang; Dongtao Cao; Fukun Xu (The Astronomical Journal)
We conducted photometric observations for transit events of three exoplanetary systems HAT-P-36, XO-2 and WASP-76 using the 1 m and 2.4 m telescopes at Yunnan Observatories and the 0.85 m telescope at National Astronomical Observatories of China. By combining the photometric data from the TESS mission, we have performed a detailed analysis for the obtained transit light curves using the Markov chain Monte Carlo technique, and obtained precise transit midtimes for the three systems. Based on our new measurements and other available transit mid-times, we have determined more accurate orbital periods for these systems. From the analysis, we find that all of these planetary systems exhibit certain transit-timing variations (TTVs). The TTV patterns are simulated by using the constant period model, orbital decay model and apsidal precession model, but we do not obtain reasonable models to account for the TTVs. Furthermore, to assess the presence of additional planets in these systems, we have constrained the masses of perturbing planets using the root mean square (rms) values of the observed TTVs and the rms values of radial velocity residuals. The results demonstrate that, under the condition of mean motion resonances, these systems may harbor perturbing planets with masses from a few tenths to more than one hundred Earth mass.